Konten Materi Aqidah Karya Haji Muhammad Saleh pada Mata Pelajaran Aqidah Akhlak di Madrasah Tsanawiyah (Telaah Kitab Syarah Aqidatul Al-Awam) - Ihsan, Muhammad; Mahrus, Erwin (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to analyze the content or content of Hajj Muhammad Saleh's work, namely the Book of Syarah Aqidatul al-Awam with the content of Aqidah Akhlak Subject Material in Madrasah Tsanawiyah. The research method used is literature study, which is an analysis of the content of the book of Syarah Aqidatul al-Awam. The results showed that the Book of Syarah Aqidatul al-Awam has enormous relevance to the subject of Aqidah Akhlak in Madrasah Tsanawiyah. This is because the content of the book can help strengthen the basics of aqidah of Madrasah Tsanawiyah students. This research also shows that Syarah Aqidatul al-Awam contains the basics of the ahlussunnah waljamaa'ah creed, which is the creed followed by most Muslims. Ahlussunnah waljamah, ahl which means group, follower, or family. As-Sunnah which means the teachings of the Prophet Muhammad SAW, either something said, deed, or confession. The Book of Sarah Aqidatul al-Awam contains Aqaid 50 which consists of 20 obligatory qualities, 20 impossible qualities, and 1 jaiz attribute for Allah. Then 4 obligatory qualities for the apostle, 4 impossible qualities, and 1 jaiznya nature. The Book of Syarah Aqidatul al-Awam is a book consisting of 57 nadzom stanzas and contains material about the creed. The material of creed in the Book of Syarah Aqidatul al-Awam has relevance to the material of creed in the subjects of moral creed at the level of Madrasah Tsanawiyah